BMSC exosomes deliver JKAP to restore Th17/Treg balance via AKT/ERK, alleviating rheumatoid arthritis - Fang-Tian Xu; Yu Ling; Hui-Xian Wei; Lingzhang Meng; Dong Yin; Zhong-Hong Lai; Yu Huang; Xiao Huang; Hai-Ye Li; Qin-Wen Luo; Jian Song; Qiang Tang; et al. (iScience, 2025)
Summary: JKAP regulates T cell immunity and inflammation in autoimmune diseases. This study investigates how bone marrow mesenchymal stem cell (BMSC)-derived exosomes deliver JKAP to restore Th17/Treg balance in rheumatoid arthritis (RA). RA CD4+ T-cells and fibroblast-like synoviocytes (RA-FLS) were treated with BMSC, exosomes, or JKAP-modified exosomes ± AKT/ERK inhibitors. BMSC/exosomes suppressed Th17 and promoted Treg differentiation, effects diminished without exosomes. JKAP knockdown impaired exosome-mediated Th17/Treg regulation and AKT/ERK activation, while overexpression enhanced these effects. JKAP-deficient exosomes increased CD4+ T cell proliferation and RA-FLS inflammation, reversed by AKT/ERK inhibition. In collagen-induced arthritis mice, exosomes alleviated symptoms and restored Th17/Treg balance, whereas JKAP knockdown exacerbated arthritis and disrupted balance. JKAP-overexpressing exosomes showed opposite effects. Thus, BMSC exosomes mitigate RA by delivering JKAP to restore immune balance via AKT/ERK pathways.